Strategies to Enhance Corrosion Resistance of Zn Electrodes for Next Generation Batteries - Lei, Longlin; Sun, Yangting; Wang, Xiangyu; Jiang, Yiming; Li, Jin (Frontiers in Materials, 2020)
Zn is an important negative electrode material in our battery industry and next-generation Zn based batteries are prospective to compete with lithium-ion batteries on cost and energy density. Corrosion is a severe challenge facing Zn electrodes, which can decrease the capacity, cyclability and shelf life of batteries. More attention should be paid to Zn electrode corrosion in developing rechargeable and high energy density Zn batteries. In this mini review, the fundamental electrochemical behavior and corrosion of Zn electrodes in aqueous environment are retrospected. Then main strategies in recent studies to mitigate Zn electrode corrosion including electrolyte additives usage, electrode composition design and electrode morphology modification are reviewed.